Particle radiation therapy in the management of malignant glioma: Early experience at the Shanghai Proton and Heavy Ion Center. Issue 12 (13th March 2020) - Kong, Lin; Wu, Jinsong; Gao, Jing; Qiu, Xianxin; Yang, Jing; Hu, Jiyi; Hu, Weixu; Mao, Ying; Lu, Jiade J.
Abstract : Background: The objective of this study was to evaluate the outcomes of patients with high‐grade glioma who received treatment with particle radiotherapy. Methods: Between June 2015 and October 2018, 50 consecutive and nonselected patients with glioblastoma multiforme (n = 34) or anaplastic glioma (n = 16) were treated at the Shanghai Proton and Heavy Ion Center. Twenty‐four patients received proton radiotherapy (at a dose of 60 gray‐equivalents in 30 daily fractions), and 26 patients received proton radiotherapy plus a carbon‐ion radiotherapy (CIRT) boost in various dose‐escalating schemes. All patients received temozolomide because of their age or their O‐6‐methylguanine‐DNA methyltransferase (MGMT) promoter methylation status. Progression‐free survival (PFS) and overall survival (OS) rates, as well as treatment‐induced toxicities, were analyzed. Results: At a median follow‐up of 14.3 months (range, 4.8‐39.6 months), the 12‐month and 18‐month OS rates were 87.8% (95% CI, 77.6%‐98.0%) and 72.8% (95% CI, 56.7%‐88.9%), respectively, and the 12‐month and 18‐month PFS rates were 74.2% (95% CI, 60.9%‐87.5%) and 59.8% (95% CI, 43.1%‐76.5%), respectively. Univariate analyses revealed that age (>50 vs ≤50 years), World Health Organization grade (3 vs 4), and Karnofsky performance status (>80 vs ≤80) were significant prognosticators for OS, and IDH mutation and World Health Organization grade were significant for predicting PFS. Furthermore, MGMT promoter methylation, performance status, and age showed a trend toward predicting PFS. No significant predictive factors for PFS or OS were identified in multivariate analyses. Twenty‐nine patients experienced grade 1 treatment‐related acute adverse effects, and 11 developed grade 1 (n = 6) or grade 2 (n = 5) late adverse effect of radiation‐induced brain necrosis. No grade 3, 4, or 5 toxicities were observed. Conclusions: Particle radiotherapy produced 18‐month OS and PFS rates of 72.8% and 59.8%, respectively, with acceptable adverse effects in patients with high‐grade glioma. Particle radiotherapy at a dose ≥60 gray‐equivalents appears to be safe and potentially effective. Abstract : Particle radiotherapy with concurrent temozolomide could potentially produce better outcomes than conventional radiotherapy plus temozolomide. Particle radiotherapy to a dose of ≥60 gray‐equivalents with concurrent temozolomide is safe for patients with high‐grade glioma.